The Future of Radiology: Exploring Emerging Technologies and Their Clinical Applications - Salman Abdullah Alhawti, Abdulkarim Nasser FahadAlharbi‏, Abdullah Saud Nasser Alzabni, Saleh Abdullah Mohammed Almuzaini, Khaled Fahad Abdullah Albaqaawi, Homoud Saud Mohammed Al-Kamees, Nabit Saeed Sumaihan Alnabit, Ghalib Salem Olyan Alshammari (Journal of International Crisis and Risk Communication Research, 2024)
Introduction: Radiology has always been one of the pillars of the medical field alongside being one of the first specialties in use in the diagnosis and management of diseases. Technological developments have moved radiology from simple and basic procedure such as x-ray to the use of modern devices such as the computed tomography (ICT), magnetic resonance imaging (MRI) and positron emission tomography (PET). Radiology has prepared to take steps forward and enter the age of rapid technological advancement in healthcare delivery. Advanced imaging systems such as ;artificial intelligence (AI), molecular imaging and hybrid imaging systems, 3D printing, and advanced interventional radiology techniques etc. are changing the dynamic of medical imaging. Aim of work: To explore the transformative impact of emerging technologies on the field of radiology, focusing on their current advancements, clinical applications, and potential future developments. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Future, Radiology, Emerging, Technologies, Clinical, and Applications. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion: It is a well-established fact that the radiology prospective is blest with unprecedented opportunities for innovation and change. Technologies like artificial intelligence, molecular and hybrid imaging systems, interventional radiology, and 3D printing are the innovative horizons that are defining the future of radiology, increasing its scope and importance in making radiology a personalized and predictive medicine. Thus, radiology will remain firmly planted on the trajectory of future development of health care, enhancing the diagnosis’s accuracy as well as the efficacy of treatment interventions and general hospital care. By overcoming the challenges that their implementation poses to the radiology community, the potential of these technologies will be realized, and a new generation of medical advancements opened up.